Sports injury prevalence and associated factors in functional fitness:a cross-sectional study - Martins Utida, Karina Ayumi; Carvalho Gomes, Denise Cruz; de Souza Ajala, Fábio; Martinez, Paula Felippe; de Oliveira-Junior, Silvio Assis (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Purpose. We investigated injury rates over the previous 12 months, associated factors, and injury characteristics in a cohortof recreational functional fitness training participants.Methods. A cross-sectional study was conducted with a convenience sample of 304 participants (175 females and 129 males;mean age: 32.6 ± 7.2 years; mean training experience: 27.6 ± 21.4 months) from three CrossFit™ affiliated gyms in Brazil.Data were collected via face-to-face interviews, using a questionnaire that focused on functional fitness-related injuries inthe previous year and included data on participant demographics and training regimens.Results. Out of all the participants, 82 (27.0%) experienced a functional fitness-related injury with an incidence rate of1.22 injuries/1000 hours of participation. The practice of other sports activities and dissatisfaction with joint mobility of theshoulders increased the odds of being injured in the multivariate logistic regression. The shoulder was the most affected bodypart (26.6%). A gradual injury mechanism was the most commonly reported (36.2%), and joint sprain (18.1%), cartilage injury(11.7%), and tendinopathy (10.6%) were the most common pathology types. Concerning symptom severity, in most cases,participants referred to the injury as severe (36.2%), with a sporting time loss greater than 28 days (50%).Conclusions. Injury prevalence over the last 12 months was 27.0% (82/304), with an incidence of 1.22 injuries/1000 hours.The practice of other sports activities and dissatisfaction with joint mobility of the shoulders increased the odds of injury. Mostinjuries occurred in the shoulder, with a gradual injury mechanism, and participants classified symptoms as severe, leadingto significant sporting time loss.
Keywords: observational study; athletic injuries; risk factors